A conciliação das elites projeto hegemônico de democracia na Revista Veja - Zen, Luis Fernando Guimarães (2009)
This research was done jointly with the Pos Graduate Program in History from the Western Paraná State University UNIOESTE. The study intended to understand how the Veja magazine acted during the Brazilian re-democratization process from 1982 to January 1985. The magazine was methodically analyzed as "a private apparatus for hegemony having as basis the theoretical studies of Antonio Gramsci. The re-democratization process experienced by the country in the 1980s was marked by popular processions in favor of the called "diretas já" (direct elections) involving many sectors of the Brazilian society, claiming the right to democracy. This study problematizes the attitude of Veja magazine during this process in which it acted in order to formulate a neo-liberal proposal claiming that this was the best alternative to solve the political, economic and social problems in the country. This magazine positioning is clear when it was formed a dissent group within the Government party, the favorite candidate in the indirect elections, situation in which emerged the called "Liberal Front" supported by Veja. The "Front" was crucial in the process as it joins the "opposition" and wins the elections even in an indirectly election.